Conservation of a Rare and Threatened Species Capparis Cartilaginea Decne. (Capparaceae) in Gujrat State-india - Pandey, R. P.; Meena, S. L.; Padhye, P. M.; Singhadiya, M. K.; Maina, Vinod; Singh, V. (Indian Forester, 2012)
The present paper deals with detailed citation, description, distributionution, phonological, ecological data, notes, uses, causes of rarity and conservation measures suggested for regeneration of Capparis cartilaginea Decne. threatened species in India. Photographs are also provided for its easy identification in the field